1983
DOI: 10.1111/j.1365-2044.1983.tb15175.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of etomidate during an intravenous infusion over 48 hours

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…fluid administration that occurred during the PK sampling. While etomidate PK is linear in adults in the dose range 0.2–0.6 mg/kg, it is possible that at the upper range of adult etomidate dosing recommendations (0.6 mg/kg) infants may not exhibit linear PK, as this has not been studied and infants may be exposed to higher plasma concentrations and durations of effect than our simulations predict . Finally, the effect of etomidate on adrenal function, which remains an important topic of debate, was not elucidated in this study.…”
Section: Discussionmentioning
confidence: 78%
“…fluid administration that occurred during the PK sampling. While etomidate PK is linear in adults in the dose range 0.2–0.6 mg/kg, it is possible that at the upper range of adult etomidate dosing recommendations (0.6 mg/kg) infants may not exhibit linear PK, as this has not been studied and infants may be exposed to higher plasma concentrations and durations of effect than our simulations predict . Finally, the effect of etomidate on adrenal function, which remains an important topic of debate, was not elucidated in this study.…”
Section: Discussionmentioning
confidence: 78%
“…The doses of etomidate used in the study are clinically relevant. It has been estimated that the peak plasma concentration of etomidate during induction of general anesthesia is approximately 10 –5 M [ 22 24 ]. The free plasma concentration is likely to be 2.5 × 10 –6 M. In addition, it has been reported that 5 × 10 –5 M concentration of etomidate is clinically relevant [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peak plasma concentration of etomidate during induction of general anaesthesia is approximately 10 -5 M 20,21 , whereas the free plasma concentration is likely to be less than 10 -5 M because about 76.5% of etomidate 22 is bound to plasma protein. Thus, the inhibitory effects of etomidate of endotheliumdependent vasorelaxation induced by acetylcholine in this study appear to be significant at clinically relevant concentrations.…”
Section: Discussionmentioning
confidence: 99%